The History of Devil Education - Cato (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
The history of the educational process on earth has been going on for a long time even before the human race was born, namely since the Jin nation. They interact with each other, socialize, establish marriage ties, promote the spirit of mutual cooperation, live in harmony, peace and prosperity and progress. However, many of them neglect the guidance of educational values taught by Allah SWT. For the arbitrary actions committed by them, Allah sent Iblis and his troops to stop their brutal actions. so that they perished which signaled the end of the life of the Jin nation on Earth. The author does not invite to have the character of Iblis, but how to actualize the educational values of Iblis in life, especially for the advancement of education. There are many good values that have been done by the Jinns. The author hopes that readers will emulate these educational values, including fear of God, honesty, courage and love challenges, critical thinking, independence and love of freedom, prioritizing logic over feelings, loyalty to speech, not easily discouraged, love of family.